Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/npp.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

40 Hz Auditory Steady-State Response Is a Pharmacodynamic Biomarker for Cortical NMDA Receptors

Abstract: Schizophrenia patients exhibit dysfunctional gamma oscillations in response to simple auditory stimuli or more complex cognitive tasks, a phenomenon explained by reduced NMDA transmission within inhibitory/excitatory cortical networks. Indeed, a simple steady-state auditory click stimulation paradigm at gamma frequency (~40 Hz) has been reproducibly shown to reduce entrainment as measured by electroencephalography (EEG) in patients. However, some investigators have reported increased phase locking factor (PLF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
106
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 69 publications
(95 reference statements)
7
106
0
Order By: Relevance
“…The suppression of high frequency gamma activity by PCP in the present study is similar to several other studies of auditory ERPs in rodents with NMDAr function impaired through genetic manipulations [25] and other NMDAr antagonists, such as MK-801 [30], ketamine [14], and PCP [28]. In contrast, relatively low dose ketamine administration in humans [27] and mice [26] failed to suppress auditory evoked gamma activity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The suppression of high frequency gamma activity by PCP in the present study is similar to several other studies of auditory ERPs in rodents with NMDAr function impaired through genetic manipulations [25] and other NMDAr antagonists, such as MK-801 [30], ketamine [14], and PCP [28]. In contrast, relatively low dose ketamine administration in humans [27] and mice [26] failed to suppress auditory evoked gamma activity.…”
Section: Discussionsupporting
confidence: 89%
“…Hall et al (2011) used a twin design and found that auditory gamma-band power and phase locking to standard tones in an auditory oddball paradigm were heritable responses associated with schizophrenia: both patients with schizophrenia and their non-psychotic co-twins showed reduced gamma power [3]. The pathophysiological mechanisms responsible for deficits in auditory gamma-band activity in schizophrenia have focused on the role of the parvalbumin-positive gamma-amino butyric acid (GABA) receptor and to N -methyl-d-aspartate receptor (NMDAr) [4,1214]. Both in vitro and in vivo evidence suggest that excitatory principal neurons, parvalbumin inhibitory interneurons, subtype A of the gamma-amino butyric acid receptor family (GABA A ), and NMDAr modulate neural synchrony in the gamma frequency range [1518].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important finding, given the increasing use of the ASSR as a biomarker in investigations of neuropsychiatric disorders (O’Donnell et al, 2013; Sivarao et al, 2016; Thune et al, 2016). Consistent with our previous findings with EEG data (McFadden et al, 2014), we found the ASSR to be reliable across two sessions, spaced approximately one week apart.…”
Section: Discussionmentioning
confidence: 78%
“…Much evidence suggests that ASSR abnormalities reflect dysfunctional gamma-aminobutyric acid (GABA) neurotransmission, leading to inefficiencies in brain inhibitory function (Brenner et al, 2009; Kwon et al, 1999; Lewis et al, 2005; O’Donnell et al, 2013; Vohs et al, 2010). However, there is also evidence suggesting that the ASSR involves glutamatergic dysfunction (Brenner et al, 2009; Kwon et al, 1999; Leishman et al, 2015; O’Donnell et al, 2013; Plourde et al, 1997; Sivarao et al, 2013; Sivarao, 2015; Sivarao et al, 2016; Vohs et al, 2012), particularly supported by emerging evidence that the 40 Hz ASSR may be more sensitive to N -methyl-D-aspartate (NMDA) receptor antagonism than to GABA-A receptor antagonism (Sullivan et al, 2015). With this growing body of evidence, the ASSR demonstrates strong potential as a biomarker in clinical studies of neuropsychiatric disorders (O’Donnell et al, 2013; Sivarao, 2015; Thune et al, 2016).…”
Section: Introductionmentioning
confidence: 99%